PERAN EMPLOYEE ENGAGEMENT SEBAGAI MEDIASI TERHADAP DETERMINAN KOMITMEN ORGANISASI DI PT. XYZ - Hotto Formandha Hutapea; Dian Surya Sampurna (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study examines the influence of employee well-being, transformational leadership, and organizational culture on organizational commitment, with employee engagement serving as a mediating variable among employees of PT XYZ in the steel manufacturing and construction sector. This study employs a quantitative approach with a causal associative research design. The research population consists of 278 employees of PT XYZ in 2024, and the sample was determined using a purposive sampling technique, resulting in 172 respondents. This number was chosen because it approaches the moderate sample size, thus categorized as adequate and considered sufficiently representative of the research population. Data were collected through questionnaires and analyzed using statistical methods to examine both direct and indirect relationships among variables. The findings reveal that: (1) employee well-being has an effect on organizational commitment; (2) transformational leadership has an effect on organizational commitment; (3) organizational culture has an effect on organizational commitment; (4) employee well-being does not affect employee engagement; (5) transformational leadership positively influences employee engagement; (6) organizational culture does not affect employee engagement; (7) employee engagement positively influences organizational commitment; (8) employee engagement does not mediate the relationship between employee well-being and organizational commitment; (9) employee engagement does not mediate the relationship between transformational leadership and organizational commitment; and (10) employee engagement does not mediate the relationship between organizational culture and organizational commitment.